LINK OF ACCIDENTAL AND NON-ACCIDENTAL IN MULTIVERSE OF IMAGINARY REALITIES - Kharchenko, Ju. V. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
It is described that the dominance of the "non-accidental" phenomenon in some conspiracy sense of the word demands its study in the scientific dimension. The main goal of the paper is to define the principle of interrelation of "accidental" and "non-accidental" in multiverse of imaginary realities. The author conceptualizes "accidental" and "non-accidental", shows their history in terms of semantic and hermeneutic approaches and states their derivation from the philosophical categories of "necessary" and "accidental". Being universal the categories of "necessary" and "accidental" represent different characteristics of the causal relationships in the ontological, epistemological and phenomenological contexts. Ontological, epistemological and phenomenological approaches reveal the deeper levels of interaction between natural and social processes. While describing accidental the author applied probability, stochastic principles. The probability is depicted as structure-mediator (conciliator, pointing to the practical scope of the intersection of accidental and non-accidental events), which provides conditional balance between their manifestations. Therefore, non-accidental is the opposite to accidental, unavoidable event; it depends on the will of the person (people), some higher-order forces. They develop mechanisms producing social life and life of the entire universe. "Accidental" is opposite to "non-accidental", it does not depend on any will.